2016
DOI: 10.3171/2015.6.jns15706
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic telescopic craniotomy: a cadaveric study of a novel device and technique

Abstract: OBJECT The authors assessed the feasibility of the dynamic decompressive craniotomy technique using a novel cranial fixation plate with a telescopic component. Following a craniotomy in human cadaver skulls, the telescopic plates were placed to cover the bur holes. The plates allow constrained outward movement of the bone flap upon an increase in intracranial pressure (ICP) and also prevent the bone flap from sinking once the ICP normalizes. The authors compared the extent of postcraniotomy ICP control after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Dynamic craniotomy enables an unhinged outward bone flap migration with an increased intracranial volume expansion compared with a hinge craniotomy 1-3 and provides another armamentarium in the management of increased ICP from postoperative complications such as brain swelling and/or rehemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic craniotomy enables an unhinged outward bone flap migration with an increased intracranial volume expansion compared with a hinge craniotomy 1-3 and provides another armamentarium in the management of increased ICP from postoperative complications such as brain swelling and/or rehemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Decompressive craniotomy is effective in controlling increased ICP and is life saving for patients with malignant strokes and traumatic brain injury. 1-7,9-17 ICP elevation is frequently encountered in severe traumatic brain injury, 18-20 malignant strokes, 5,6,21-25 aneurysmal subarachnoid hemorrhage, 26-28 intracerebral hemorrhage, 29-31 and brain tumors. 32,33 Uncontrollably elevated ICP has also been associated with poor patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is further reinforced by a biomechanical study in human cadaver skulls [ 30 ], which compared DC to HC and ‘dynamic decompressive craniotomy’ and the effect on ICP after abrupt increase in intracranial volume. They found that both the dynamic craniotomy and the HC techniques provided significant control of ICP during 120 ml increase in intracranial volume as compared with craniotomy rigidly fixed with plates (4.86 mmHg, 8.36 mmHg, 44.84 mmHg, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the patients included in the studies of the present scoping review are not directly comparable to the RESCUEicp population but this figure can give an indication as to the proportion of patients with refractory ICP despite DC. This concept is further reinforced by a biomechanical study in human cadaver skulls [30], which compared DC to HC and 'dynamic decompressive craniotomy' and the effect on ICP after abrupt increase in intracranial volume. They found that both the dynamic craniotomy and the HC techniques provided significant control of ICP during 120 ml increase in intracranial volume as compared with craniotomy rigidly fixed with plates (4.86 mmHg, 8.36 mmHg, 44.84 mmHg, respectively).…”
Section: Intracranial Pressurementioning
confidence: 99%
“…4 The idea of expanding intracranial volume is not unique to the field of epilepsy surgery involving implantation of intracranial electrodes but has been explored in the context of cerebral edema from traumatic brain injuries and stroke. 6,9,13 Compared with other situations in which efforts have been made to reduce the number of necessary surgeries (e.g., when a bone flap rises relative to the surrounding calvaria in response to intracranial hypertension but settles downward with resolution of cerebral edema), electrode implantation surgery invariably needs to be followed by another surgery for removal of the electrodes. Therefore, it is possible to secure and keep the bone flap elevated during monitoring using the described technique, as this can be easily reversed during the second surgery.…”
Section: Discussionmentioning
confidence: 99%